2022
DOI: 10.3390/ijerph191610240
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Asymmetry Analysis between Left and Right Wrist with Sensory and Infrared Thermography

Abstract: This article reports a thermal analysis of the wrists to analyze the behavior and recovery of skin temperature after 20 min when performing a highly repetitive movement, and two thermography methods (sensory and infrared) and research groups were compared. The tests were carried out with 44 participants who performed a repetitive task for 10 min and integrated into two groups, of which 22 were trained workers from a maquiladora company and were analyzed with sensory thermography, and the other 22 were in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The study analyses and compares PPG recordings of responders and non-responders (NR) to PBM. The criterion for dividing the participants into responders (n = 12) and non-responders (n = 8) in the original study was an increase of ≥0.5 °C which is accepted as a deviation from the normal symmetrical thermal distribution between sides of the body extremities (Ammer, 2012;Garcia Becerra et al, 2022) and was found to indicate underlying pathologies (Suominen and Asko-Seljavaara, 1996;Selfe et al, 2008). In the original study (Gavish et al, 2020), this criterion was used as a threshold for dynamic changes in thermal response to PBM.…”
Section: Study Overviewmentioning
confidence: 99%
“…The study analyses and compares PPG recordings of responders and non-responders (NR) to PBM. The criterion for dividing the participants into responders (n = 12) and non-responders (n = 8) in the original study was an increase of ≥0.5 °C which is accepted as a deviation from the normal symmetrical thermal distribution between sides of the body extremities (Ammer, 2012;Garcia Becerra et al, 2022) and was found to indicate underlying pathologies (Suominen and Asko-Seljavaara, 1996;Selfe et al, 2008). In the original study (Gavish et al, 2020), this criterion was used as a threshold for dynamic changes in thermal response to PBM.…”
Section: Study Overviewmentioning
confidence: 99%
“…Thus, training load control has been important in reducing the risk of injuries and improving performance [ 1 , 12 ]. On the other hand, fatigue would be related to loss of speed and metabolic stress [ 12 , 13 ]. Allied with this, the decrease in asymmetries would be related to improvements in function, strength, and power.…”
Section: Introductionmentioning
confidence: 99%
“…Digital infrared thermographic imaging (DITI) has been utilized as an ancillary diagnostic method for various medical conditions related to the upper extremities. For instance, cervical radiculopathy; peripheral nerve entrapment syndrome (e.g., carpal tunnel syndrome); rheumatic disease (e.g., Raynaud’s disease); complex regional pain syndrome; tendinopathy; hand arthritis (e.g., psoriatic arthritis); and skin cancer can be confirmed by DITI [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. The hypo-radiant (hypothermia) or hyper-radiant (hyperthermia) regions can be identified by comparing the temperature between the right and left arms or with empirical normal ranges.…”
Section: Introductionmentioning
confidence: 99%